2010
DOI: 10.1051/0004-6361/201014468
|View full text |Cite
|
Sign up to set email alerts
|

The Supernova Legacy Survey 3-year sample: Type Ia supernovae photometric distances and cosmological constraints

Abstract: Aims. We present photometric properties and distance measurements of 252 high redshift Type Ia supernovae (0.15 < z < 1.1) discovered during the first three years of the Supernova Legacy Survey (SNLS). These events were detected and their multi-colour light curves measured using the MegaPrime/MegaCam instrument at the Canada-France-Hawaii Telescope (CFHT), by repeatedly imaging four one-square degree fields in four bands. Follow-up spectroscopy was performed at the VLT, Gemini and Keck telescopes to confirm th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
600
2
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 514 publications
(621 citation statements)
references
References 85 publications
15
600
2
4
Order By: Relevance
“…The SNLS "combined" compilation consists of 123 SNe Ia at low redshifts, 242 SNe Ia from the three-year Supernova Legacy Survey (SNLS; see Regnault et al 2009;Guy et al 2010;Conley et al 2011), 93 intermediate redshift SNe Ia from the Sloan Digital Sky Survey (SDSS; Holtzman et al 2008;Kessler et al 2009) and 14 objects at high redshift observed with (HST; Riess et al 2007).…”
Section: The Snls Compilationmentioning
confidence: 99%
“…The SNLS "combined" compilation consists of 123 SNe Ia at low redshifts, 242 SNe Ia from the three-year Supernova Legacy Survey (SNLS; see Regnault et al 2009;Guy et al 2010;Conley et al 2011), 93 intermediate redshift SNe Ia from the Sloan Digital Sky Survey (SDSS; Holtzman et al 2008;Kessler et al 2009) and 14 objects at high redshift observed with (HST; Riess et al 2007).…”
Section: The Snls Compilationmentioning
confidence: 99%
“…1 for supernovae of type Ia, assuming M = -19.3. The data include the SALT2 analysis of the Constitution set (Hicken et al 2009), the Union2 set (Amanullah 2010), and the SNLS-3 set (Guy et al 2010). In cases in which the same object occurred in more than one of these sets, the data from the analysis that reported the least uncertainty in m were used.…”
Section: Redshift Magnitude and Distancementioning
confidence: 99%
“…The USC includes only SNe with an official designation assigned by CBAT. About 300 SNe from high-redshift surveys are not covered (Riess et al 2007;Guy et al 2010). Fig.…”
Section: Statistical Studies With the Uscmentioning
confidence: 99%